A Cross-Cultural Comparison of Ethical Attitudes of Business Managers: India Korea and the United States - Christie, P. Maria Joseph (Journal of business ethics, 2003)
Culture has been identified as a significant determinant of ethical attitudes of business managers. This research studies the impact of culture on the ethical attitudes of business managers in India, Korea and the United States using multivariate statistical analysis. Employing Geert Hofstede's cultural typology, this study examines the relationship between his five cultural dimensions (individualism, power distance, uncertainty avoidance, masculinity, and long-term orientation) and business managers' ethical attitudes. The study uses primary data collected from 345 business manager participants of Executive MBA programs in selected business schools in India, Korea and the United States using Hofstede's Value Survey Module (94) and an instrument designed by the researchers to measure respondents' ethical attitudes (attitudes toward business ethics in general and toward twelve common questionable practices in particular). Results indicate that national culture has a strong influence on business managers' ethical attitudes. In addition to national culture, respondents' general attitudes toward business ethics are related to their personal integrity; their attitudes toward questionable business practices are related to the external environment and gender, as well as to their personal integrity. A strong relationship exists between cultural dimensions of individualism and power distance and respondents' ethical attitudes toward certain questionable practices. The analysis of the relationship between cultural dimensions of masculinity, uncertainty avoidance and long-term orientation and respondents' ethical attitudes toward questionable practices produced mixed results, likely due to the lack of notable differences in cultural dimension scores among the countries surveyed.